Pengaruh Manajemen Pajak terhadap Pajak Penghasilan Badan (pada Perusahaan Manufaktur di BEI) - Khasanah Sahara; Devia Oktafiani (Universitas Islam Kadiri, 2022)
This study aims to determine the effect of tax management on corporate income tax (in manufacturing companies on the Indonesia Stock Exchange). The research variable is the issuance of Tax Management (X), Corporate Income Tax (Y). Collecting data using the documentation method, data on the sample companies' financial statements are available on the Indonesia Stock Exchange which can be accessed through the website www.idx.co.id. The researcher accessed the data through the Indonesian Stock Exchange's Sharia Investment Gallery at the Kadiri Islamic University. Based on the results of the research data analysis as stated in the previous chapter, it can be concluded as follows: There is an effect of tax management by companies on corporate income tax in manufacturing companies on the Indonesia Stock Exchange for the 2016-2018 period. This is based on research findings which found that from seven sample companies, only KAEF companies had an effective tax rate and cash effective tax rate above 25% continuously in the 2016-2018 range. Meanwhile, companies that continuously avoided taxes during 2016-2018 were SMSM companies. Suggestions that can be given are in accordance with the research results, namely tax avoidance as one of the company's efforts to carry out tax management in general, it can be legally carried out by companies, but this condition will certainly reduce the potential for tax revenue that should be acceptable to the state. It is important to raise awareness for companies not to evade taxes because this will harm state revenues and even disrupt development processes in the long term. For the government, it can provide tax payment incentives so as to encourage companies to properly report tax obligations which are the responsibility of the company